Qatar National Library’s efforts in opening up Qatar’s research output a step towards a global open access transformation - Alwaleed Alkhaja (13761787) (2023)
This presentation was given by Alwaleed K. Alkhaja, Qatar National Library  Open access can provide a global solution that addresses restrictions in the interlibrary loan(ILL) or document delivery services for electronic resources. The use of academic electronicresources for ILL transactions is governed and often limited by licenses between librariesand various publishers. In an ideal situation, libraries would not require ILL or a documentdelivery for electronic resources; instead, they would rely on openly licensed material. Such a digital utopia, where all research content is available under an open license, is perhaps not yet attainable, but efforts worldwide are slowly transitioning the academic landscape. In this paper, we would like to describe our efforts at Qatar National Library for the last three years in transforming Qatar’s research output into OA. Besides providing an accessible archive of Qatar’s research, our goal has been to improve the reach of Qatar’s research to a global audience. We will describe our licensing principles, which addresses OA publications and maximize access rights for interlibrary loans, course packs and classroom use, and perpetual access. In addition, we would like to describe how our efforts are part of a global push to shift costs from access to publishing. We are at the crossroads where we need to ensure a sustainable transition, which depends on all stakeholders in the research ecosystem (both locally and on a global stage). For OA to be a global solution, it will need concerted efforts from all international counterparts. In this paper, we also will present our ideas of how we hope to improve the OA adoption moving forward, including local and regional OA advocacy, effective centralized cost-sharing through consortia, improving repository infrastructure that can support pre-prints/green OA, and a need for more licensing transparency and improved data sharing between institutions.